Utility of Vajikarana in General Health- A Review - Anusree Dileep,; Sreelekshmi.S,; Vandana Rani M,; Delvin.T.Robin,; Meera.S, (International Journal of Ayurveda and Pharma Research, 2021)
Objective: Vajikarana or Vrishya chikitsa is the branch of Ayurveda dealing with reproductive health and virility. Though this branch makes use of drugs under the category of aphrodisiac, the multifaceted effect of those is underexplored. The properties of disease prevention and restoration of health might be the attribute benefited in sexual health too. This paper intends to explore the general health benefits of Vajikarana drugs.Materials and Methods:  Data related to the aphrodisiac drugs are located in classical texts of Ayurveda and online journals with keywords “Vajikarana, Ayurveda, aphrodisiacs, neuro-endocrine immune system, Vrishya chiktsa, Ojas and sex hormones”. The relevant scripts were selected and appropriate data from 8 articles and 18 chapters were extracted for the final manuscript construction.Results: The drugs like Ashwgandha, Shatavari, Atmagupta, Sweta musali and Masha proved to have a neuro-endocrinological effects, psycho-neuro-immunological effects, anti-inflammatory and anti-oxidant properties apart from aphrodisiac effects. It stabilizes Tridosha, Saptadathu and eventually Ojas, and calms mental faculties.Conclusion: The proper use of the Vajikarana formulations imparts qualities like good physique, potency, strength, and complexion. This benefits of Vajikarana can be incorporated into other health conditions also. The practice of Vajikarana corrects the deformities of reproductive systems and in turn balances other body functions. Advanced research on the health benefits and enhancing sexual potency of women should be carried out on Vajikarana therapy. This will aid prevention of diseases which is a major health standpoint in the current day scenario.